Local Elections and Consumption Insurance : Evidence from Chinese Villages - Gan, Li (World Bank, Washington, DC, 2012)
While the literature on consumption insurance is growing fast, little research has been conducted on how rural consumption insurance is affected by democracy. In this paper the authors examine how consumption insurance of Chinese rural residents is affected if the local leader is democratically elected. Exploring a unique panel data set of 1,400 households from 1987 to 2002, they find that consumption insurance is more complete when the households are in villages with elected village leaders. Furthermore, democracy improves consumption insurance only for the poor and middle-income farmers, but not for the rich. These findings underline the importance of democratic governance for ensuring better rural consumption insurance and poverty reduction.